β1-adrenergic receptor but not β2 mediates osteogenic differentiation of bone marrow mesenchymal stem cells in normotensive and hypertensive rats - Alves Barreto, Ayná Emanuelli [UNESP]; Balera Brito, Victor Gustavo [UNESP]; Patrocinio, Mariana Sousa [UNESP]; Ballassoni, Beatriz Babeto [UNESP]; Tfaile Frasnelli, Sabrina Cruz [UNESP]; Penha Oliveira, Sandra Helena [UNESP] (Elsevier, 2021)
The sympathetic nervous system regulates bone remodeling via adrenergic receptors on the surface of bone cells. Herein, we evaluated the role of beta-adrenergic receptors (ADRBs) in osteoblastic differentiation of bone marrow mesenchymal stem cells (BMSCs) derived from normotensive (Wistar) and spontaneously hypertensive rats (SHRs). BMSCs were cultured in a proliferation medium or osteogenic medium (OM). Cells cultured in OM were treated with carvedilol (Cv) or nebivolol (Nb).In OM, cell proliferation was decreased in both strains. In Wistar rats, Cv increased BMSC proliferation and increased alkaline phosphatase (ALP) activity in OM. Both Cv and Nb decreased ALP activity. In addition, Cv and Nb reduced mineral deposition in Wistar rats. Moreover, NB decreased mineralization in SHRs, exhibiting superior efficacy. In OM, cells from Wistar rats and SHRs showed Adrb1 and Adrb2 expression. On day 7, Nb, but not Cv, reduced Adrb1 levels in BMSCs from Wistar rats. Nb inhibited Adrb2 in both strains, and Cv demonstrated superior efficacy. In BMSCs from Wistar rats, both antagonists inhibited Runx2, osterix, and β-catenin; in SHRs, Cv and Nb inhibited only osterix. Cv decreased osteopontin (Opn), osteocalcin (Ocn), and bone morphogenetic protein (Bmp2) in BMSCs from Wistar rats, inhibiting only Opn in SHRs. Nb effectively inhibited Ocn, bone sialoprotein, and Bmp2, but not Ocn, in BMSCs from Wistar rats, while suppressing Opn in BMSCs from SHRs. In addition, Nb inhibited p-p38 in BMSCs from Wistar rats; Cv inhibited p-p38 in BMSCs from SHRs. In Wistar rats, both antagonists inhibited p-ERK and reduced p-JNK; Cv reduced these expressions only in SHRs. In conclusion, ADRB1, but not ADRB2, could be involved in the osteogenic differentiation of BMSCs from Wistar rats and SHRs. The high ADRB1 expression might suppress the effect of ADRB2 on BMSCs.
Keywords: Hypertensive rats; Normotensive; Osteogenic differentiation; β-adrenergic receptor